Non-invasive Assessment of Neurovascular Coupling After Aneurysmal Subarachnoid Hemorrhage: A Prospective Observational Trial Using Retinal Vessel Analysis - Albanna, Walid; Conzen, Catharina; Weiss, Miriam; Seyfried, Katharina; Kotliar, Konstantin; Schmidt, Tobias Philip; Kuerten, David; Hescheler, Jürgen; Bruecken, Anne; Schmidt-Trucksäss, Arno; Neumaier, Felix; Wiesmann, Martin; et al. (Frontiers in Neurology, 2021)
Objective Delayed cerebral ischemia (DCI) is a common complication after aneurysmal subarachnoid hemorrhage (aSAH) and can lead to infarction and poor clinical outcome. The underlying mechanisms are still incompletely understood, but animal models indicate that vasoactive metabolites and inflammatory cytokines produced within the subarachnoid space may progressively impair and partially invert neurovascular coupling (NVC) in the brain. Because cerebral and retinal microvasculature are governed by comparable regulatory mechanisms and may be connected by perivascular pathways, retinal vascular changes are increasingly recognized as a potential surrogate for altered NVC in the brain. Here, we used non-invasive retinal vessel analysis (RVA) to assess microvascular function in aSAH patients at different times after the ictus. Methods Static and dynamic RVA were performed in 70 aSAH patients during the early (d0-4), critical (d5-15), late (d16-23) phase, and at follow-up (f/u> 6weeks) after the ictus. For comparison, an age-matched cohort of 42 healthy subjects was also included in the study. Vessel diameters were quantified in terms of the central retinal arterial and venous equivalent (CRAE,CRVE). Vessel responses to flicker light excitation (FLE) were quantified by recording the maximum arterial and venous dilation (MAD,MVD), the time to 30% and 100% of maximum dilation (tMAD30,tMVD30;tMAD,tMVD resp.) and the arterial and venous area under the curve (AUCart,AUCven) during the FLE. For subgroup analyses, patients were stratified according to the development of DCI. Results Vessel diameter (CRAE,CRVE) was significantly smaller in aSAH patients. In addition, aSAH patients exhibited impaired arterial but not venous responses to FLE on d0-4 (MAD, p=0.0016; AUCart, p=0.0001). However, gradual recovery was observed during the first three weeks, with close to normal levels at follow-up. Finally, patients with DCI showed opposite changes in the kinetics of arterial responses during early and late phase, as reflected in a significantly lower tMAD30 on d0-4 (p=0.022) and a significantly higher tMAD on d16-23 (p=0.017). Conclusion Our findings confirm and extend previous observations that aSAH results in sustained impairments of NVC in the retina. DCI may be associated with characteristic changes in the kinetics of retinal arterial responses. However, further studies will be required to determine their clinical implications.